O efeito do tratamento medicamentoso da artrite reumatoide na periodontite: uma revisão sistemática - Mendonça, Milena Oliveira Mota (2024)
Periodontitis is characterized as an inflammatory oral disease, mediated by the host and associated with microorganisms present in the dental biofilm, while rheumatoid arthritis (RA) is defined as a chronic inflammatory disease of unknown etiology and characterized by irreversible joint destruction. Although a causal relationship between periodontitis and RA has not yet been completely established, studies have already demonstrated an increased incidence of periodontitis in patients with RA when compared to healthy individuals. Furthermore, studies also indicate that new biological therapies used in the treatment of RA have been shown to be effective in improving the clinical and radiological signs of periodontitis. Thus, the objective was to evaluate the effect of treatment with disease-modifying antirheumatic drugs (DMARDs) in patients with rheumatoid arthritis and periodontitis, without having received periodontal treatment during the study, through a systematic review. A search was carried out in databases and gray literature: Medline, Lilacs, Pubmed, Embase, Scopus, Livivo, Cochrane, Web Of Science, Google Scholar, Pubmed Central and Open Thesis. Inclusion criteria: studies that were randomized controlled clinical trials; studies in which all participants had RA and periodontitis concomitantly; studies with a clear clinical definition of periodontitis, assessed by the parameters of probing pocket depth (PPD) and clinical attachment loss (CAL); studies in which patients with RA and periodontitis had received drug treatment for RA; studies published in any language. Exclusion criteria: studies other than randomized controlled clinical trials; studies in which participants presented only one of the conditions, periodontitis or RA in isolation; studies that did not present a clear definition for periodontitis; studies in which participants suffered from other systemic conditions capable of affecting their periodontal condition; studies in which participants had received periodontal therapy within the previous 6 months. The systematic review sample was composed of 5 primary studies, carried out in 3 different countries, and published between 2013 and 2021. Among the medications used by the authors, we can mention disease-modifying antirheumatic drugs (DMARDs), specifically, conventional synthetic DMARDs, such as methotrexate (MTX), leflunomide (LEF), sulfasalazine (SSZ) and hydroxychloroquine (HCQ) and biological DMARDs, such as Tocilizumab (TCZ), adalimumab (ADA), rituximab ( RTX), infliximab (IFX), etanercept (ETN). As primary results, it was shown that antirheumatic agents were beneficial in improving PS, and three of the four studies that evaluated CIN also showed a significant reduction in this parameter. Among the secondary outcomes, the present review showed that antirheumatic agents were beneficial in improving the gingival index (GI) and bleeding on probing (SS) in patients suffering from RA and periodontitis concomitantly. Thus, this systematic review suggests evidence to characterize the correlation between these two conditions and that drug therapy for RA can bring improvements to the periodontal parameters of patients who have periodontitis and RA concomitantly.